A field investigation into the effect of under sleeper pads on the reduction of railway-induced ground-borne vibrations. (March 2016) - Ali Zakeri, Jabbar; Esmaeili, Morteza; Heydari-Noghabi, Hamidreza
Train-induced vibrations have adverse effects on the structure of a track and its surroundings. It is thus necessary to study and control this issue through efficient measures. Special polyurethane pads that are placed under sleepers have been recently suggested as a solution to this problem. The use of these pads reduces vibrations at their source. These pads, called under sleeper pads (USPs), have numerous advantages and have found wide application in the railway industry. However, very few studies have been conducted on USPs; thus, this paper presents a field study that documents their effects on reducing vibration levels. Fifty stiff and 100 soft pads were prepared with the required technical and mechanical specifications. They were then installed onto concrete sleepers during the production process. These sleepers were installed at km-253 of the Mashhad–Tehran track. Train pass-by vibrations of passenger and freight trains were recorded using geophones placed at 0, 3, 7, 11, 15 and 19 m distances from each track axis (one track with and one without USPs). The results of the tests show that the maximum root-mean-square velocity was reduced by about 60%. Frequency analysis of the results demonstrates that the vibration reduction effect of the USPs appears above 40 Hz. The best efficiency levels of the USPs were observed in the range 40–80 Hz and the maximum USP efficiency occurred at the frequency of 50 Hz. At this specific frequency, the maximum vibration velocity level was decreased by more than 6.7 dB for all the considered distances (0, 3, 7, 11, 15 and 19 m).